(untitled) (Advances in Systems Science and Applications, 2017)
Methods of measurement and prediction of materials dynamic strength are complicated and not standardized. Usually dynamic tests are labour-consuming and each assay demands a lot of time in contrast to static experiments. The way of experimental data treatment based on incubation time criterion and randomized approach of sign-perturbed sums is considered. It is shown that a few experimental points are enough to determine strength parameter with accuracy proper for engineering. The lack of real experimental data is compensated in SPS-algorithm by carrying out a large number of virtual random tests in which the Bernulli signs are randomly generated in this method.